Kontribusi Masyarakat terhadap Eksplorasi Bambu sebagai Material Konstruksi Hunian Humanis di Pedesaan - Imriyanti, Imriyanti; ., Nasruddin; Mushar, Pratiwi; ., Hartawan; Arisaputra, Andi Lolo Sinrang; Arsyal, Andika; Amalia, Reski; Maisi, Marzon; A., Muh. Nurhalim (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2024)
Most housing materials are made of manufactured materials so that houses/residences do not give the impression of being one with their environment. The large use of manufactured materials causes building materials that are easily obtained around housing or organizations to no longer be utilized, such as bamboo. Houses in Kalase'rena sub-district predominantly use manufactured materials so that the use of bamboo as a Natural Resource (SDA) is no longer utilized, with the reduced use of bamboo as a housing/residence material, how is the role of the community/its contribution in exploring it as a humanistic housing material. The purpose of this service is to increase the community's contribution to the exploration of natural materials in community housing buildings that can be integrated with their environment, reduce costs and increase the level of community togetherness. The service was carried out by distributing questionnaires, identification and direct meetings with the Kalase'rena sub-district community. The initial response from the community to the use of bamboo as a humanistic housing material was very minimal (2%). This service achievement is that the role and understanding of the community towards the processing of bamboo as a humanistic housing material has increased from the economic (90%) and social (94%) fields. This influences the public's understanding of humanist housing which is very beneficial for the community directly in the Kalase'rena sub-district.